COVID-19 outcomes in patients with a history of immune-mediated glomerular diseases - Gauckler, Philipp; Kesenheimer, Jana S.; Geetha, Duvuru; Odler, Balazs; Eller, Kathrin; Laboux, Timothee; Alberici, Federico; Zappa, Mattia; Chebotareva, Natasha; Moiseev, Sergey; Bonilla, Marco; Jhaveri, Kenar D.; et al. (Frontiers in Immunology, 2023)
Introduction: Patients with immune-mediated glomerular diseases are considered at high risk for severe COVID-19 outcomes. However, conclusive evidence for this patient population is scarce. Methods: We created a global registry and retrospectively collected clinical data of patients with COVID-19 and a previously diagnosed immune-mediated glomerular disease to characterize specific risk factors for severe COVID-19 outcomes. Results: Fifty-nine patients with a history of immune-mediated glomerular diseases were diagnosed with COVID-19 between 01.03.2020 and 31.08.2021. Over a mean follow-up period of 24.79 ± 18.89 days, ten patients (16.9%) developed acute kidney injury. Overall, 44.1% of patients were managed in an outpatient setting and therefore considered as having “non-severe” COVID-19, while 55.9% of patients had severe COVID-19 requiring hospitalization including worse outcomes. Comparing both groups, patients with severe COVID-19 were significantly older (53.55 ± 17.91 versus 39.77 ± 14.95 years, p = .003), had lower serum albumin levels at presentation (3.00 ± 0.80 g/dL versus 3.99 ± 0.68 g/dL, p = .016) and had a higher risk of developing acute kidney injury (27% versus 4%, p = .018). Male sex (p < .001) and ongoing intake of corticosteroids at presentation (p = .047) were also significantly associated with severe COVID-19 outcomes, while the overall use of ongoing immunosuppressive agents and glomerular disease remission status showed no significant association with the severity of COVID-19 (p = .430 and p = .326, respectively). Conclusion: Older age, male sex, ongoing intake of corticosteroids and lower serum albumin levels at presentation were identified as risk factors for severe COVID-19 outcomes in patients with a history of various immune-mediated glomerular diseases.